2019
DOI: 10.1021/acsomega.8b02872
|View full text |Cite
|
Sign up to set email alerts
|

Helical Contributions Mediate Light-Activated Conformational Change in the LOV2 Domain of Avena sativa Phototropin 1

Abstract: Algae, plants, bacteria, and fungi contain flavin-binding light-oxygen-voltage (LOV) domains that function as blue light sensors to control cellular responses to light. In the second LOV domain of phototropins, called LOV2 domains, blue light illumination leads to covalent bond formation between protein and flavin that induces the dissociation and unfolding of a C-terminally attached α helix (Jα) and the N-terminal helix (A′α). To date, the majority of studies on these domains have focused on versions that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…8 This appears to stabilize the interaction between A’α and Jα, which was previously shown by Zayner and coworkers to be important for the unfolding of the Jα helix as observed by FTIR. 28 The TRIR and NMR spectra show that N414 is responsible for stabilizing the Jα helix in the dark state and that this helix is partially unfolded in the N414A mutant which has a critical impact on LOV domain function since the N414A LOVTRAP mutant has lost the ability to interact with the Zdk2 peptide in a light dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This appears to stabilize the interaction between A’α and Jα, which was previously shown by Zayner and coworkers to be important for the unfolding of the Jα helix as observed by FTIR. 28 The TRIR and NMR spectra show that N414 is responsible for stabilizing the Jα helix in the dark state and that this helix is partially unfolded in the N414A mutant which has a critical impact on LOV domain function since the N414A LOVTRAP mutant has lost the ability to interact with the Zdk2 peptide in a light dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…A marker band for unfolding of the Jα helix was identified in the amide I region, ∼1620-1640 cm −1 using difference FTIR. 2628 TRIR experiments revealed that helix unfolding was multi-step, 29 and that structural changes resulting from adduct formation follow dispersive kinetics commonly associated with sampling of multiple protein conformations prior to reaching a metastable state, which is the signaling state in LOV domain proteins. 30 TRIR spectroscopy of multiple LOV domain proteins revealed variations in the dynamics of the β-sheet and the Jα helix, which link the LOV domain to the relevant effector domains.…”
Section: Introductionmentioning
confidence: 99%
“…However, the A390 EADS curve resembles the steady-state spectrum of EL222 obtained under continuous illumination 32 and therefore contains changes in protein secondary, tertiary and possibly quaternary structure (oligomerisation). More specifically, unfolding of the A 0 a-helix, 57,90 unfolding of Ja-helix, 28,88,91 and rearrangement of beta-sheets 90 have been postulated in the spectral region between 1620 and 1670 cm À1 of many LOV domains. While the aforementioned large-scale effects are not incorporated in the current computational setup, the good agreement of the computed Qc pertains mostly to features above baseline, hinting that quite a few of those features can be assignable to small-scale effects.…”
Section: Ir Difference Spectramentioning
confidence: 99%
“…The key intermediates along the photocycle were modelled and analysed vibrationally, producing difference spectra, which were then correlated with the experimental infrared spectra of the EL222 and AsLOV2 proteins from this work and the literature. 7,32,57 Since both the photocycle and the spectroscopic analysis are presented here through the prism of the key glutamine residue, the possibility of imidic tautomerisation of its side chain was also considered for the LOV domains (Scheme 1). This was highlighted before in BLUF, 37,53,[58][59][60][61] a class of blue-light absorbing photoreceptors sharing the isoalloxazine ring.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these studies are performed in truncated proteins that may lead to artifacts due to construct length. Indeed, recent studies of AsLOV2 have demonstrated that the N‐terminal A′α helix is required for light‐driven Jα unfolding, and constructs containing A′α extensions can attenuate conformational changes in the Jα helix .…”
Section: Discussionmentioning
confidence: 99%